Behoteguy Chávez, G. (2023). Memorias de pacto y terror. Historias del general René Barrientos Ortuño en Bolivia (1959-1969) - Botero Aristizabal, Andrey Nicolás (2025)
Fil: Botero Aristizabal, Andrey Nicolás. Universidad Nacional de La Plata, Argentina.